2019
DOI: 10.3390/nano9030432
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Synthesized Si@C Materials for the Lithium Ion Battery: A Mini Review

Abstract: As an important component, the anode determines the property and development of lithium ion batteries. The synthetic method and the structure design of the negative electrode materials play decisive roles in improving the property of the thus-assembled batteries. Si@C compound materials have been widely used based on their excellent lithium ion intercalation capacity and cyclic stability, in which the in-situ synthetic method can make full use of the structural advantages of the monomer itself, thus improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Compared with a simple physical mechanical mixing synthesis method, the in-situ synthesis method for the as-prepared catalysis displays a more uniform structure. Moreover, this in-situ synthesis method provides a strategy for forming a tight-contact heterostructure between two compounds [61]. From the eco-friendly and chemical stability view, tin oxide (SnO2) was employed as a promising photocatalyst [62].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with a simple physical mechanical mixing synthesis method, the in-situ synthesis method for the as-prepared catalysis displays a more uniform structure. Moreover, this in-situ synthesis method provides a strategy for forming a tight-contact heterostructure between two compounds [61]. From the eco-friendly and chemical stability view, tin oxide (SnO2) was employed as a promising photocatalyst [62].…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that the influence of three different contact modes of silicon and coating on the electrochemical performance of silicon anode should be drowned more attention. Although there have been some researches focusing on material design, [ 28,19 ] surface and interface engineering, [ 67,68 ] structural design, [ 69,70 ] mechanism research, [ 71,72 ] and composite and coating engineering with carbon materials, [ 73,74 ] the influence of contact engineering between core and coating on the performance of silicon anode has not been systematically summarized. Based on this, this review will start from the contact engineering according to the three contact modes of F2F, L2L and P2P, detail its influence on ion/electron transfer and electrochemical performance of silicon anode, and summarize the structural design direction which is conducive to improve the performance of silicon anode for the reference to researchers.…”
Section: Contact Engineeringmentioning
confidence: 99%
“…For the selected electric motor, the different types of commercial batteries available were taken into account: Acid lead, NiMH, NiCd, LiPo, and LiFePO4, although new materials for batteries in aerospace and aeronautical applications will be available in the coming years [79][80][81]. However, with the actual state of technology and market prices, it was concluded that the best battery to be used in the electric ALO is the lithium polymer (LiPo) battery.…”
Section: New Electronic Power Systemmentioning
confidence: 99%